2017
DOI: 10.1073/pnas.1705441114
|View full text |Cite
|
Sign up to set email alerts
|

In vivo loss-of-function screens identify KPNB1 as a new druggable oncogene in epithelial ovarian cancer

Abstract: Epithelial ovarian cancer (EOC) is a deadly cancer, and its prognosis has not been changed significantly during several decades. To seek new therapeutic targets for EOC, we performed an in vivo dropout screen in human tumor xenografts using a pooled shRNA library targeting thousands of druggable genes. Then, in follow-up studies, we performed a second screen using a genome-wide CRISPR/Cas9 library. These screens identified 10 high-confidence drug targets that included well-known oncogenes such as ERBB2 and RAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 47 publications
6
77
1
Order By: Relevance
“…Kodama M recently reported that ivermectin initiates multiphase cell cycle arrest and apoptosis in epithelial ovarian cancer (EOC) cells, which is consistent with the alterations observed after KPNB1 suppression. 10 In addition, another investigation demonstrated that ivermectin induces apoptosis in glioblastoma and HeLa cells by enhancing cytochrome c release, upregulating Bax and p53 expression, downregulating Bcl-2 expression and decreasing the levels of cyclin E, cyclin D1, CDK2, CDK6 and CDK4. 26,27 Ivermectin Induces Immunogenic Cell Death (ICD)…”
Section: Ivermectin Induces Caspase-dependent Apoptosismentioning
confidence: 99%
“…Kodama M recently reported that ivermectin initiates multiphase cell cycle arrest and apoptosis in epithelial ovarian cancer (EOC) cells, which is consistent with the alterations observed after KPNB1 suppression. 10 In addition, another investigation demonstrated that ivermectin induces apoptosis in glioblastoma and HeLa cells by enhancing cytochrome c release, upregulating Bax and p53 expression, downregulating Bcl-2 expression and decreasing the levels of cyclin E, cyclin D1, CDK2, CDK6 and CDK4. 26,27 Ivermectin Induces Immunogenic Cell Death (ICD)…”
Section: Ivermectin Induces Caspase-dependent Apoptosismentioning
confidence: 99%
“…In research to screen potential targets for the treatment of ovarian cancer through the use of an shRNA library and a CRISPR/Cas9 library, the oncogene KPNB1 was detected. IVM could block the cell cycle and induce cell apoptosis through a KPNB1-dependent mechanism in ovarian cancer [ 59 ]. Interestingly, IVM and paclitaxel have a synergistic effect on ovarian cancer, and combined treatment in in vivo experiments almost completely inhibited tumor growth.…”
Section: The Role Of Ivm In Different Cancersmentioning
confidence: 99%
“…An experiment found that IVM could significantly enhance the inhibitory effects of erlotinib and cetuximab on lung cancer and colorectal cancer [ 50 ]. Earlier, we mentioned that IVM combined with conventional chemotherapeutic drugs such as cisplatin [ 60 ], paclitaxel [ 59 ], daunorubicin and cytarabine [ 51 ], or with targeted drugs such as dasatinib [ 53 ] and dapafenib [ 73 ] shows great potential for cancer treatment. The combination of drugs can effectively increase efficacy, reduce toxicity or delay drug resistance.…”
Section: Anticancer Effect Of Ivm Through Other Pathwaysmentioning
confidence: 99%
“…The screening component was introduced in non‐metastatic mouse cancer cells and, then, they were transplanted into adult mice and tumor growth‐ and metastasis‐related mutations were screened. After this publication, various related studies depending on the transplantation‐based approach have been conducted . In addition, adeno‐associated virus (AAV) vector‐mediated direct delivery of pooled sgRNA library enabled bona fide in vivo screening, although the capacity of the library size was tightly restricted in this strategy (Figure B, top arrow) .…”
Section: A Closer Look At Front‐line Technologiesmentioning
confidence: 99%
“…After this publication, various related studies depending on the transplantation-based approach have been conducted. [41][42][43] In addition, adeno-associated virus (AAV) vector-mediated direct delivery of pooled sgRNA library enabled bona fide in vivo screening, although the capacity of the library size was tightly restricted in this strategy ( Figure 4B, top arrow). 44,45 Such ex vivo and in vivo screening studies were nicely summarized recently by Chow and Chen.…”
Section: Genome-wide Screeningmentioning
confidence: 99%